Reallocating time to physical activity and sleep: associations with quality of life and body mass index in cancer survivors - Hidde, Mary, author; Leach, Heather, advisor; Broussard, Josiane, committee member; Lyden, Kate, committee member; Henry, Kim, committee member (Colorado State University. Libraries, 2021)
Introduction: Quality of Life (QOL) and Body Mass Index (BMI) are important outcomes for cancer survivors due to their association with cancer-related morbidity and mortality. Lifestyle behaviors including physical activity (PA), sedentary time, and sleep are all potential intervention targets to improve QOL and BMI. The effect of these activities on QOL and BMI is most often studied in isolation despite the interdependent nature of these behaviors; time cannot be increased in one activity without decreasing time in another. Since these behaviors are often studied in isolation, it is difficult to assess if an improvement in QOL or BMI is attributed to increasing positive behaviors (i.e., PA or sleep), or decreasing negative behaviors (i.e., sedentary time). The growing interest around 24-hour activity patterns has increased researcher interest in objective measurement of PA and sleep using accelerometers. However, this currently requires researchers to utilize one device to measure sleep (i.e., Actiwatch) and one to measure waking behaviors (i.e., activPAL). This has led to high research costs and burden since the Actiwatch cannot measures waking behaviors and, until recently, the activPAL could not detect time in bed (TIB), limiting researcher's ability to objectively collect 24-hour activity data. In order to move the world of 24-hour activity forward and delineate the role time reallocations throughout the day affect pertinent cancer-related outcomes, additional research must be conducted to explore solutions to the high research costs and burden associated with 24-hour activity measurement. Therefore, the purpose of this dissertation is to (1) evaluate if the new activPAL algorithm designed to measure TIB can estimate TIB similarly to the valid and reliable Actiwatch and 2) evaluate, using an Isotemporal substitution model, the effects of reallocating time from one activity to another on QOL and BMI using accelerometry (Actiwatch and activPAL pending results of aim 1) to measure 24-hour activities. Methods: The activPAL algorithm's ability to measure TIB was evaluated using a cross-sectional analysis of participants (n=85) undergoing a time-restricted feeding study. Participants (for all studies) wore the activPAL accelerometer to measure waking behaviors and the Actiwatch to measure sleeping behaviors for 7 days, 24-hours per day. Repeated measures mixed effects models and Bland-Altman plots were used to compare the activPAL TIB estimates to the Actiwatch TIB estimate with type of device and day of wear as fixed effects and participant as a random effect. TIB results were then utilized in a cross-sectional analyses of cancer survivors (n=73) within 60 months of surgery, chemotherapy, and/or radiation. In addition to wearing the activPAL and Actiwatch, participants completed the Functional Assessment of Cancer Therapy-General (FACT-G) to measure QOL. Participants self-reported height and weight to calculate BMI. Demographics were calculated using mean ± standard deviation or frequencies (%). Isotemporal substitution models were used to evaluate the effects of reallocating 30 minutes of each activity to another. Statistical significance for all studies was set at p<.05. Results: The activPAL accelerometer does not estimate TIB similarly to the Actiwatch. Additionally, no significant interaction was observed for type of accelerometer and day of wear. There were no statistically significant reallocations for total QOL score or the included subscales. However for BMI, reallocating 30 minutes of sleep to sedentary time or moving 30 minutes of sedentary time to light PA did result in statistically significant changes in BMI. There were no statistically significant reallocations by moving moderate-vigorous PA to other activities of interest. Despite no statistical significance for QOL, reallocating time from sedentary time or light PA to MVPA resulted in clinically meaningful increases in QOL (>4 points). Conclusion: Estimates of TIB from the activPAL and Actiwatch accelerometers were not similar, suggesting that researchers who are interested in the 24-hour activity cycle will continue to require the use of both accelerometers to measure both sleep and active/waking behaviors. Results of reallocating time on QOL and BMI indicate that in addition to MVPA, sleep, and light PA are essential behaviors for cancer survivors. The work presented in this dissertation can provide a starting point for the development of 24-hour activity guidelines for improving BMI and QOL in cancer survivors; however, additional time reallocation studies using a larger sample size in order to include bouted and non-bouted activity time as well as more detailed measures of body composition (i.e., dual x-ray absorptiometry) are needed to further understand the role the 24-hour activity cycle has on BMI and QOL in cancer survivors.
Keywords: physical activity; sedentary time; BMI; sleep; QOL